(untitled) (Texas Journal of Multidisciplinary Studies, 2024)
Freedom of expression, or freedom of speech, is essential to a democracy. It means that everyone can participate in political debates, and the media holds those in power accountable. A free, independent and diverse media plays the role of “protecting the public interest” by informing the public and holding government accountable